Sarbanes-Oxley and the new internal auditing rules - Moeller, Robert R. (John Wiley & Sons, Inc. HobokenUS, 2004)
Explains the Sarbanes-Oxley Act, how it impacts auditors, and how internal auditing can help its requirements, such as launching an ethics and whistle-blower programme or performing effective internal control reviews under the Committee Sponsoring Organizations (COSO) framework.